OPTIMIZATION OF BIOGAS PRODUCTION FROM TREE WASTE MATERIALS FOR BIORESOURCE RECOVERY (FUDMA JOURNAL OF SCIENCES, 2023)
Biogas production from waste biomass has gained significant attention as a sustainable alternative to conventional fossil fuels. This study investigated the potential of using tree waste materials for biogas production and optimizing the process parameters. A lab-scale anaerobic digester was used to evaluate the biogas generation potential of tree trimmings and sawdust. Different process parameters, including the substrate-to-inoculum ratio, temperature, and pH, were varied to optimize the biogas yield. We also analyzed the chemical composition of the feedstock and the digestate to assess nutrient recovery potential. The results showed that tree trimmings and sawdust are suitable feedstocks for biogas production, with a maximum biogas yield of 228.4 mL CH4/g VS added obtained at a substrate-to-inoculum ratio of 2:1 and a temperature of 35°C. The nutrient analysis showed that the digestate obtained from the anaerobic digestion process is a rich source of nitrogen, phosphorus, and potassium, which can be used as fertilizer.
Keywords: Biogas; methane yield; methanogenic microorganisms; substrate degradation rate; tree waste